THE ESSENCE OF THE COMMUNICATIVE CULTURE OF AN ECONOMIST - Ірина Ярищук (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The expediency of formation of the skills of communication culture in the process of training of future economists to foreign language communication has been grounded. The concept of "communication culture" has been determined. The essence of communication culture of an economist has been defined. It has been proved that communicative culture is one of the most important components of professional competence of an economist. It has been concluded that the professional competence of the economist, in addition to the personal and business skills, provides the ability and skills to ensure the functioning of the communication process. The author has determined such structural components of communicative culture of the economist: ideological, motivational, communicative, emotional and volitional, constructive.